Chemical composition of edible aerial parts of meadow bistort (Persicaria bistorta (L.) Samp.). (1st September 2017) - Klimczak, Urszula; Woźniak, Marta; Tomczyk, Michał; Granica, Sebastian
Highlights: UHPLC method for the analysis of aerial parts of common bistort is reported. Twenty phenolic compounds were isolated and identified. Two new natural products were obtained and their structure was elucidated. Tested compounds display potential anti-inflammatory activity. Abstract: Persicaria bistorta (syn. Polygonum bistorta ) is a herbaceous plant native to Europe and Asia. The leaves, young shoots or aerial parts of bistort are one of the main ingredients in a savoury pudding common to parts of the North of England. The aim of the present study was to investigate the chemical composition of extracts from aerial parts of common bistort. The UHPLC method allowed the detection of thirty-five major and minor compounds in the analysed plant material. Major constituents were isolated and identified. Two new natural products were obtained namely quercetin and kaempferol 3- O -(5″- O- malonyl) - α-l -arabinofuranosides. The bioactivity assays showed that isolated malonylated flavonoids inhibit the production of reactive oxygen species (IC50 in the range 22.4–40.6 μM) and myeloperoxidase release (IC50 in the range 22.2–32.2 μM) from stimulated human neutrophils. Aerial parts of P. bistorta are a rich source of polyphenols and some of them have anti-inflammatory potential.